Sea Monsters: Things from the Sea, Volume 2 - Tomaini, Thea; Mittman, Asa Simon (punctum books, 2017)
Beaches are places that give and take, bringing unexpected surprises to society, and pulling essentials away from it. Through monsters, we confront our tiny time between catastrophes and develop a recognition of Otherness by which an ethical understanding of difference becomes possible. Learning to read the monster's environmental signs often helps humans determine the scope of the monster's place in the eco/cosmic timeline and defeat it-until the epic cycle inevitably repeats; monsters live and live and live. Even so; when humans identify and confront monsters we do so at the risk of exposing our own monstrosity. When a massive creature is pushed into human proximity by the ocean's wide shoulders, the waves deposit and erode human assumptions about itself and its environment; words, sounds, breath, water, wind, flesh, blood, and bones wash in and out. Chance encounters reveal us to ourselves anew. When we look into the inky backs of whales, or deep into vortices, what do we see?